Kilka uwag na temat nauczania aspektu polskiego czasownika - PÁTROVICS, PÉTER (SlavVaria, 2021)
Some Remarks On Teaching Polish Verbal Aspect. The present paper draws attention to some problems related to the teaching of the Polish verbal aspect, while also shedding light on the possible theoretical linguistic back-ground of the description of the Slavic aspect category. The author examines the category of the Slavic verbal aspect in terms of two possible approaches: cognitive linguistics and functional grammar emphasizing the importance of teaching aids: a structural aspect dictionary of the Polish verb and teaching manuals presenting the theories about the Polish verbal aspect.